2006
DOI: 10.1063/1.2372317
|View full text |Cite
|
Sign up to set email alerts
|

Submicrosecond dynamics of water explosive boiling and lift-off from laser-heated silicon surfaces

Abstract: Explosive boiling and lift-off of a thin layer of micron-sized transparent water droplets from an absorbing Si substrate heated by a nanosecond KrF laser were studied using a contact photoacoustic technique. The compressive photoacoustic response increases steeply to an asymptotic value on the order of the water critical pressure starting at a threshold laser fluence of 0.20J∕cm2, where lift-off of the water layer also occurs. Above this threshold, several reproducible discrete multimegahertz components are re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 38 publications
1
11
0
Order By: Relevance
“…The TiO 2 NPs and GO platelets could be ejected as part of the water droplets generated in the process of explosive boiling of the overheated water matrix. Indeed, photoacoustic studies of water droplets deposited on the surface of absorbing Si wafers and heated with a nanosecond KrF* excimer laser, at the same fluence value as used in our experiments, proved the onset of explosive boiling of superheated water, by nucleation of interfacial steam nanobubbles, followed by their coalescence to microbubbles and their further lift-off . In a MAPLE experimental configuration similar to ours, metal based acetates in water matrix were irradiated with KrF* excimer laser at laser fluence values comparable to that used by us .…”
Section: Resultssupporting
confidence: 56%
See 1 more Smart Citation
“…The TiO 2 NPs and GO platelets could be ejected as part of the water droplets generated in the process of explosive boiling of the overheated water matrix. Indeed, photoacoustic studies of water droplets deposited on the surface of absorbing Si wafers and heated with a nanosecond KrF* excimer laser, at the same fluence value as used in our experiments, proved the onset of explosive boiling of superheated water, by nucleation of interfacial steam nanobubbles, followed by their coalescence to microbubbles and their further lift-off . In a MAPLE experimental configuration similar to ours, metal based acetates in water matrix were irradiated with KrF* excimer laser at laser fluence values comparable to that used by us .…”
Section: Resultssupporting
confidence: 56%
“…Indeed, photoacoustic studies of water droplets deposited on the surface of absorbing Si wafers and heated with a nanosecond KrF* excimer laser, at the same fluence value as used in our experiments, proved the onset of explosive boiling of superheated water, by nucleation of interfacial steam nanobubbles, followed by their coalescence to microbubbles and their further lift-off. 50 In a MAPLE experimental configuration similar to ours, metal based acetates in water matrix were irradiated with KrF* excimer laser at laser fluence values comparable to that used by us. 51 After initial photothermal decomposition of acetate molecules under the excimer laser irradiation, new absorption centers, decomposition products, metal ions, and oxide NPs were created.…”
Section: Resultsmentioning
confidence: 99%
“…As briefed in the introduction, there are still some debates about whether vapor bubbles could be formed on top of heated nanoparticles using MD simulation. There have been recently some experimental studies demonstrated that the physical existence of nanobubbles or microbubbles around small particles ,, . For instance, by applying X-ray scattering to the laser excited particle solution, Plech and Kotaidis et al , showed that gold particles of 9 nm diameter could be excited by a nanosecond laser to produce large vapor bubbles that decayed within less than 1 nanosecond.…”
Section: Discussionmentioning
confidence: 99%
“…The PA technique has been used to study different laser-matter interactions processes in liquids, such as: ablation of solids immersed in liquids [27], the formation of organic nanocrystals during the irradiation of microcrystals [26], the microbubbles systems dynamics [34,36], the formation and evolution of nanobubbles around nanoparticles [29], shock waves generated by the implosion of the cavitation bubble [33,37], the measurement of acoustic speed and thermal-acoustic transformation coefficient of an absorbing liquid [35].…”
Section: Introductionmentioning
confidence: 99%